Electrical Capacitance Volume Tomography (ECVT) for real-time brain activity monitoring: a comparative frequency analysis study - Hanin Aisya Fakihati; Seftina Diyah Miasary; Marlin Ramadhan Baidillah (Journal of Holistic Medical Technologies (JHMT), 2025)
Current brain imaging modalities such as CT scan and MRI, while providing excellent anatomical detail, have limitations in real-time functional brain activity monitoring. Electrical Capacitance Volume Tomography (ECVT) emerges as a promising non-invasive, cost-effective alternative for dynamic brain activity assessment. This study aims to evaluate the sensitivity of ECVT technology in detecting brain motor activity variations across different frequencies and determine the optimal frequency for brain wave fluctuation measurement. A 16-electrode ECVT helmet system was employed to monitor brain activity in subjects performing motor stimulation tasks including hand gripping, imagined movement, and control conditions (water and empty space). Measurements were conducted at three frequency variations: 500 kHz, 1 MHz, and 5 MHz. Data acquisition involved multiple channel combinations (C14-16, C14-15, C14-13, C14-12, C16-15, C16-9, C16-8, C16-10) with voltage peak-to-peak (Vpp) measurements recorded via oscilloscope. The 500 kHz frequency demonstrated the highest sensitivity in detecting brain activity variations. Distinct Vpp patterns were observed across different motor tasks, with imagined movement producing the highest values, indicating increased neural activity. The ECVT system successfully differentiated between active motor tasks and resting states. ECVT at 500 kHz frequency shows superior sensitivity for brain activity monitoring, offering a portable, low-cost alternative to conventional neuroimaging modalities for real-time functional brain assessment.